Identification of surface active components in glass forming melts by thermodynamic model - Chromcikova, Maria; Hruska, Branislav; Svoboda, Roman; Liska, Marek; Nowicka, Aleksandra; Bruneel, Els; De Buysser, Klaartje (Elsevier Science BV, 2021)
Nine compositional series of 15(Na2O, K2O).10(CaO, ZnO).75(ZrO2, SiO2) glass-forming melts were studied, all with the ZrO2 content of 0, 1, 3, 5 and 7 mol.%. The investigated glass compositions were obtained by equimolar substitutions ZrO2 / SiO2, ZnO / CaO and K2O / Na2O. Surface tension of studied glassforming melts was determined by the sessile and pendant drop profile numerical analysis in the temperature range (1250 1500) °C. The experimental values of melt density were used. The linear temperature dependence of surface tension was observed for all samples with only small differences between values obtained from sessile and pendant drop profiles. The Shakhmatkin and Vedishcheva thermodynamic model (TDM) was evaluated for each glass melt at temperature of 1400 degrees C. The total number of 36 components was considered in TDM. Only 26 components were present with non-negligible equilibrium amount. The surface tension was described by the multilinear function of equilibrium amounts of statistically independent non-negligible components of the TDM. The surface active components were identified by negative values of their coefficients. Such way the N3S8 and C2ZrS4 were identified as "strongly" surface active and NCS5 and KS4 as probably surface active. Regarding the oxide compositional point of view, the surface tension was mostly influenced by ZnO (increase with the addition of the oxide) and by K2O (decrease with the addition of the oxide).
Identifikace povrchově aktivních komponent ve sklotvorných taveninách pomocí termodynamického modelu
Keywords: surface tension; sessile and pendant drop; thermodynamic model; surface active components; povrchové napětí; termodynamický model; povrchově aktivní látky